(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
A walk down memory lane of Kashmir always accentuated the disturbing shadow of conflicts,human- rights violation, mindless political ventures and so on. From foreign invaders to the currentpolitical urges, the Kashmir or Kashmiris have been witnessing chaos and devastation be it social,political, cultural or economical facets. The popular discourse of Kashmir or Kashmiris has been underthe shadow of doubt as it does not reflect depredation and persecution in its totality. The present paperseeks to bring back the articulation of local narratives thereby contemplating over the dual perspectiveto look upon death like conditions of Kashmiris be it muslims or Kashmiri pandits. The present papertries to scrutinize over the pathetic conditions out of political and religious upheavals while undertakingthe parallel reading of saga as one from Muslim community other from Brahmin community who at theend share some common condition of victimization.